2006
DOI: 10.1577/m05-135.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Native and Introduced Flathead Catfish Populations in Alabama and Georgia: Growth, Mortality, and Management

Abstract: We compared growth of flathead catfish Pylodictis olivaris from two native populations in Alabama (Coosa and Tallapoosa rivers) and two introduced populations in Georgia (Ocmulgee and Satilla rivers). We also compared mortality rates and potential outcomes of various management regimes (minimum length limits [MLLs]) among the populations. Total length–log10(age) regression slopes for introduced fish were higher than those for native fish, and von Bertalanffy growth coefficients (K) were greater for introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 6 publications
2
58
0
Order By: Relevance
“…The only other estimate of annual mortality for a flathead catfish population in lentic waters came from at Lake Wilson, Alabama (17%; Marshall et al 2009), and was lower than for Lake Mitchell. Estimates for lotic populations range from about 12%-36% (Daughtery & Sutton 2005;Kwak et al 2006;Makinster & Paukert 2008;Jolley & Irwin 2011;Kaeser et al 2011), however, values similar to Lake Mitchell were reported for the Missouri River (34%-59%, Gavin's Point Dam to the Kansas-Nebraska border; Goble 2011) and the Satilla River, Georgia (45%; Sakaris et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…The only other estimate of annual mortality for a flathead catfish population in lentic waters came from at Lake Wilson, Alabama (17%; Marshall et al 2009), and was lower than for Lake Mitchell. Estimates for lotic populations range from about 12%-36% (Daughtery & Sutton 2005;Kwak et al 2006;Makinster & Paukert 2008;Jolley & Irwin 2011;Kaeser et al 2011), however, values similar to Lake Mitchell were reported for the Missouri River (34%-59%, Gavin's Point Dam to the Kansas-Nebraska border; Goble 2011) and the Satilla River, Georgia (45%; Sakaris et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Although flathead catfish occur in modified river systems and may be fluvial generalists, these fish were more abundant along natural river banks compared to revetted bank in the Mississippi River (Pennington et al, 1983). Growth of flathead catfish is related to the environment (river or reservoir) or if the population is native or introduced (Kwak et al, 2006;Sakaris et al, 2006). However, little information exists on the variability in growth among reaches or habitats within a river.…”
Section: Introductionmentioning
confidence: 99%
“…Extensively introduced outside its native range (Fuller et at. 1999), the flathead catfish has altered the composition of native fish populations through predation (Pine et al 2005, Sakaris et al 2006, Pine et al 2007). The growth of flathead catfish varies extensively from population to population (Grabowski et al 2004, Kwak et al 2006, but there is a general trend that reservoir residents grow faster than riverine individuals, introduced flathead catfish grow faster than those in native populations, and individuals in eastern United States populations grow more rapidly than those in western populations (Kwak et al 2006).…”
Section: Introductionmentioning
confidence: 99%